ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BACA GENERASI Z PADA ERA DIGITAL - Abd Muhib A.H Ntau; Jhilbrina Sarindat (Jurnal Ilmiah Widya Sosiopolitika, 2025)
The growing concern over declining minat baca among Generasi Z in the era digital forms the background of this study. This research aims to analyze the factors influencing reading interest among Generation Z in the context of rapid technological advancement. The study employed a quantitative survey method involving 350 respondents aged 15–24, supported by statistical analysis using multiple regression to identify dominant contributing variables. The findings reveal that digital accessibility, family literacy environment, and school-based reading programs significantly affect reading interest, while social media exposure shows a mixed impact depending on content type. Moreover, the study identifies a new pattern in which digital‐native readers prefer interactive and visually enriched texts over traditional formats. The study concludes that strengthening digital literacy, improving the availability of high-quality digital reading materials, and integrating technology-enhanced reading strategies are essential to increasing reading interest among Generation Z